PRESENTASI MASKULINITAS TOKOH DALAM NOVEL BEKISAR MERAH KARYA AHMAD TOHARI: ANALISIS TEORI JANET SALTZMAN CHAFETZ - Adina Anisnaeni Rizqina; Dyah Wardani Adesetia; Muhammad Aditya Wisnu Wardana; Ngifat Khoerunnisa; Sumarwati Sumarwati; Andayani Andayani (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
Discourse of masculinity is a discussion that is widely presented in literary works. Although not expressed directly, forms of masculinity appear in line with the process of telling the behavior of existing male characters. Bekisar Merah is a novel by Ahmad Tohari which represents masculinity through various male characters. Each character has a different background, giving rise to different thoughts and actions. The concept of masculinity according to Janet Saltzman Chafetz can be seen from the male aspects in the form of (1) physical aspects; (2) functional aspects; (3) sexual aspect; (4) emotional aspects; (5) intellectual aspects; (6) interpersonal aspects. This study aims to describe the form of presentation of masculinity and its causative factors in Ahmad Tohari's Novel Bekisar Merah according to Janet Saltzman Chafetz's theory. The source of the data in this research is the document of the novel Bekisar Merah by Ahmad Tohari. The data collection technique used in this study was document analysis using the look-and-note method, in which the author first reads the contents of the novel carefully, then records any important findings. Then the validity of the data was tested by theoretical triangulation to check its suitability with Janet Saltzman Chafetz's theory of masculinity. The results of this study found that there were 47 data presenting six aspects of Janet Saltzman Chafetz's masculinity in Ahmad Tohari's novel Bekisar Merah.